Niche differentiation in rainforest ant communities across three continents - Grevé, Michael E; Houadria, Mickal; Andersen, Alan N; Menzel, Florian (Ecology and evolution, 2019)
A central prediction of niche theory is that biotic communities are structured by niche differentiation arising from competition. To date, there have been numerous studies of niche differentiation in local ant communities, but little attention has been given to the macroecology of niche differentiation, including the extent to which particular biomes show distinctive patterns of niche structure across their global ranges. We investigated patterns of niche differentiation and competition in ant communities in tropical rainforests, using different baits reflecting the natural food spectrum. We examined the extent of temporal and dietary niche differentiation and spatial segregation of ant communities at five rainforest sites in the neotropics, paleotropics, and tropical Australia. Despite high niche overlap, we found significant dietary and temporal niche differentiation in every site. However, there was no spatial segregation among foraging ants at the community level, despite strong competition for preferred food resources. Although sucrose, melezitose, and dead insects attracted most ants, some species preferentially foraged on seeds, living insects, or bird feces. Moreover, most sites harbored more diurnal than nocturnal species. Overall niche differentiation was strongest in the least diverse site, possibly due to its lower number of rare species. Both temporal and dietary differentiation thus had strong effects on the ant assemblages, but their relative importance varied markedly among sites. Our analyses show that patterns of niche differentiation in ant communities are highly idiosyncratic even within a biome, such that a mechanistic understanding of the drivers of niche structure in ant communities remains elusive.
Keywords: niche partitioning; interspecific competition; community structure; coexistence mechanisms; Formicidae